2008
DOI: 10.1002/prca.200780068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variations in sample handling on SELDI‐TOF MS serum protein profiles for colorectal cancer

Abstract: Sample handling can have a profound effect on serum protein profiles, challenging results obtained with archived sera under non‐standardized sample collection. Here, we evaluate the influence of variations in sample handling on previous serum protein profiles for colorectal cancer (CRC) (Engwegen et al.,. World J. Gastroenterol. 2006, 12, 1536–1544). Sera were prospectively obtained from individuals with an indication for colonoscopy (n = 150: 65 controls, 52 adenomatous polyps, 29 CRC, 4 unknown), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…has been described previously by our group (22). We observed the N-terminal albumin fragment to be positively correlated with duration of storage (1.4 years) at -308C.…”
Section: The Albumin Clusterssupporting
confidence: 84%
See 2 more Smart Citations
“…has been described previously by our group (22). We observed the N-terminal albumin fragment to be positively correlated with duration of storage (1.4 years) at -308C.…”
Section: The Albumin Clusterssupporting
confidence: 84%
“…The susceptibility of detected proteins to sample handling issues has been discussed in previous studies (8,22,31). A number of these proteins have, however, also been reported as potential cancer markers (10,11,21).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Differences between samples frozen for 1-3 months at -208C or -808C have not been observed in several studies (16,26,34). However, this may be due to the short storage times because another research group reported that most differences became apparent after about 5 months of storage (35). One peptide noted to be altered by storage at low temperature was a biomarker previously identified as a candidate for colorectal cancer, an N-terminal albumin fragment (m/z 3087).…”
Section: Preanalytical Phasementioning
confidence: 97%
“…False discovery can exert a distinct influence on the serum proteome, potentially leading to significant differences between results, even with comparable patient populations and sample types under study. [22][23][24][25][26] New proteomic technologies that promote large-scale sample screening and facilitate identification of proteins associated with disease and treatment are developing rapidly. 27,28 Mass spectrometry (MS), a powerful proteomics tool, has evolved to a high-throughput level, allowing rapid and accurate analysis of several thousand proteins in a single study.…”
Section: Introductionmentioning
confidence: 99%